2016
DOI: 10.1371/journal.pone.0163252
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cytokine Expression and STAT3 Activation between Healthy Controls and Patients of Unexplained Recurrent Spontaneous Abortion (URSA) during Early Pregnancy

Abstract: Unexplained recurrent spontaneous abortion (URSA) is a common complication of pregnancy. Although tolerance of the maternal immune system is considered to be essential for a normal pregnancy, the precise mechanism underlying the pathogenesis of URSA remains to be fully elucidated, albeit it is known to involve inflammation. Here, we examine the relationship between the expression of inflammatory cytokines and the activation of downstream signaling pathways in URSA patients. Decidual and peripheral blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Th17 cells and promotes the secretion of IL-17. The increased expression of IL-23 and IL-17 in women with RPL was reported in previous studies 83. In this study, RPL was significantly negatively correlated with 25(OH)D, suggesting that low VD levels in decidual tissues were associated with RPL and VD might play a vital role in influencing the IL-23/IL-17 axis.…”
supporting
confidence: 78%
“…Th17 cells and promotes the secretion of IL-17. The increased expression of IL-23 and IL-17 in women with RPL was reported in previous studies 83. In this study, RPL was significantly negatively correlated with 25(OH)D, suggesting that low VD levels in decidual tissues were associated with RPL and VD might play a vital role in influencing the IL-23/IL-17 axis.…”
supporting
confidence: 78%
“…Interleukin-23 (IL-23) can promote Th17 cell differentiation and maintain the Th17 response. In a previous study, we found increased IL-17 and IL-23 expression in women with RSA ( 16 ). Therefore, it is becoming clear that immune disturbances are involved in the pathogenesis of RSA ( 17 ).…”
Section: Introductionmentioning
confidence: 65%
“…Western blotting was used to measure the expression of VDR and CYP27B1 in decidual tissues following a previously described method ( 16 ). Briefly, total protein was isolated from each decidual tissue sample and mixed with 5× sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) loading buffer (Baomanbi, China) at 4:1 v/v.…”
Section: Methodsmentioning
confidence: 99%
“…In inflammatory bowel disease mice, there was a reduction of CD4 + T cells producing IFN‐γ, an increased frequency of the putative regulatory population of T cells producing IL‐10, and an increment in the frequency of the regulatory markers GITR, CTLA‐4, PD‐1, CD73, and FoxP3, after treating with glucocorticoid (Sales‐Campos et al, ). We have found that the serum concentration of IL‐10 in patients with URSA is much lower than that in healthy controls, whereas the expression of IL‐17 is at a higher level (Cai, Li, Huang, Fu, & Wu, ). It was reported by a recent study that the patients with URSA who received immunotherapy got an increment of Treg cells and an reduction of IL‐2 level.…”
Section: Discussionmentioning
confidence: 98%